Analysis of Students‘ Error in Learning of Quadratic Equations : Systematic Literature Review - Islamiyah, Wafa; Suryadi, Didi (Universitas PGRI Madiun, 2023)
Quadratic equations are an important topic in mathematics at the secondary school level because this topic is widely used in solving problems in subsequent materials such as functions, logarithms, trigonometry, and several other materials. However, many students still make mistakes in solving quadratic equation problems. This study aims to get an overview of student errors in solving quadratic equation problems. The method used in this research is a systematic literature review. After going through the inclusion and quality test stages, the literature reviewed was 12 articles. The results of this study show that there are several student errors in quadratic equation material, namely concept errors, procedural errors, and operation errors and the factors that cause them are students not understanding the problem well, not understanding the sequence of steps used to solve the problem, and not being careful in calculating the final result, forgetting, answering originally and rushing in calculating.